(untitled) (Veterinária Notícias, 2021)
A black howler monkey (Alouatta caraya) infant, aged approximately three months, presented with a transverse fracture of the distal third of the humeral diaphysis. The monkey underwent surgical treatment using a bridge plate with an intramedullary pin. A 1.00-mm diameter intramedullary pin was used in a retrograde fashion to reduce both the fracture and plate stress. The plate was a 1.5 mm seven-hole reconstruction installed following the principles of biological osteosynthesis. The animal presented no pain in the postoperative exams and used the limb normally. Bone consolidation was observed in the eighth week after surgery, showing that the treatment was effective.